Trends in research participant categories and descriptions in abstracts from the International BCI Meeting series, 1999 to 2016. Issue 1 (3rd April 2019) - Eddy, Brandon S.; Garrett, Sean C.; Rajen, Sneha; Peters, Betts; Wiedrick, Jack; McLaughlin, Deirdre; O'Connor, Abigail; Renda, Ashley; Huggins, Jane E.; Fried-Oken, Melanie
ABSTRACT: Much brain-computer interface (BCI) research is intended to benefit people with disabilities (PWD), though they are rarely included as study participants. When included, a range of clinical and non-clinical descriptions are used leading to difficulty interpreting and replicating results. We examined trends in inclusion and description of study participants with disabilities across six International BCI Meetings from 1999 to 2016. Meeting abstracts were analyzed by trained independent reviewers. Results suggested declines in participation by PWD across Meetings until the 2016 Meeting. Fifty-eight percent of abstracts identified PWD as end-users, though only twenty-two percent included participants with disabilities, suggesting evidence of a persistent translational gap. Increased diagnostic specificity was noted at the 2013 and 2016 Meetings. Studies often identified physical and/or communication impairments in participants with disabilities versus impairments in other areas. Implementing participatory action research principles and user-centered design strategies within BCI research is critical to bridge the translational gap.